To the pathogenesis of experimental lung fibrosis in animals (clinical and hematological research) - Surtaieva, Y.; Mazurkevich, A. (Scientific Progress & Innovations, 2022)
The group of diseases called "interstitial lung diseases" in veterinary medicine, as well as in human medicine, is understudied. These diseases are based on irreversible diffuse changes in lung tissue. This is a fairly large heterogeneous group of disorders of non-infectious, non-neoplastic origin, which are characterized by a variety of manifestations in the form of inflammation and fibrosis. Establishing the mechanisms of lung tissue recovery due to fibrosis is e xtremely important for the search and use of effective means of eliminating this pathological process and restoring the functional capacity of the lungs. Purpose: to investigate the clinical manifestations and features of changes in hematological indicators in animals with experimental pulmonary fibrosis in order to substantiate their significance in the diagnosis and treatment of its clinical forms. The experimental form of pulmonary fibrosis in female Wistar rats was modeled by the method of one -time transthoracic installation of bleomycin hydrochloride solution, which is known to specifically induce the development of the fibrotic process in lung tissue and the development of pulmonary fibrosis. In order to control the changes in the animals' bodies during the formation of experimental pulmonary fibrosis, regular clinical examinations of experimental animals were carried out, as well as analysis of laboratory blood test indicators. Blood samples for laboratory analyzes were taken at baseline and on the 7th, 14th, 30th, and 45th days after administration of bleomycin hydrochloride solution to the animals in accordance with the experimental scheme. The main hematological indicators were determined in the blood samples using an automatic hematological analyzer according to the instructions attached to it. According to the results of the conducted research, we established changes in a number of other hematological indicators, namely, probable changes in the quality indicators of erythrocytes - the development of heterogeneity (heterogeneity) of erythrocyte populations in the form of anisocytosis (changes in the average volume of erythrocytes) as a result of increased intensity of erythrocyte decay and disruption of erythrocyte maturation processes or as a result of their destruction. Conclusions: the pathogenesis of fibrotic lung diseases in animals is insufficiently studied. This requires further in-depth study of the main pathogenetic mechanisms of the course of the pathological process, on experimental models of this disease for the development and further application of new methods and means of effective treatment.